The lenalidomide/bortezomib/dexamethasone regimen for the treatment of blastic plasmacytoid dendritic cell neoplasm. Issue 4 (4th September 2019) - Marmouset, Vincent; Joris, Magalie; Merlusca, Lavinia; Beaumont, Marie; Charbonnier, Amandine; Marolleau, Jean‐Pierre; Gruson, Bérengère
Abstract: We describe the use and value of a lenalidomide/bortezomib/dexamethasone regimen for the treatment of three patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN, a disease that lacks a consensus treatment). After five cycles of chemotherapy, we observed two complete responses and one clinical remission. Together with the encouraging literature data on the effects of lenalidomide and bortezomib on BPDCN cells, our results might prompt further investigations of this regimen's value in BPDCN.